Bornean felids in and around the Imbak Canyon conservation area, Sabah, Malaysia - Henry Bernard; Jedediah F. Brodie; Anthony J Giordano; Abdul Hamid Ahmad; Waidi Sinun (Cat Specialist Group, 2013)
We photo-captured three of the five species of Bornean felids in and around the Imbak Canyon Conservation Area in central Sabah, Malaysian Borneo - the Sunda clouded leopard Neofelis diardi, marbled cat Pardofelis marmorata and leopard cat Prionailurus bengalensis. The Sunda clouded leopard was the most frequently photographed felid (11 photos), followed by marbled cat and leopard cat (2 photos each). The Sunda clouded leopard and marbled cat are classified as Vulnerable on the IUCN/SSC Red List of Threatened Species, whereas the leopard cat is a species of Least Concern (IUCN 2012). All three species were detected within primary and logged forest habitats. These findings may indicate that, in addition to primary forests, regenerating secondary forests are important to felids conservation.